Oral health-related quality of life of older adults living in long-term care facilities and its association with dental prosthesis use and condition - Mariana Marinho Davino de Medeiros; Mayara Abreu Pinheiro; Olivia Maria Costa de Figueredo; Luiz Fabrício Santos de Oliveira; Rayssa Lucena Wanderley; Yuri Wanderley Cavalcanti; Renata Cunha Matheus Rodrigues Garcia (Brazilian Society of Geriatrics and Gerontology, 2023)
Objective: This cross-sectional study aimed to evaluate the association of oral health-related quality of life with prosthetic rehabilitation status and dental prosthesis condition in residents of Brazilian long-term care facilities. Methods: The oral health-related quality of life of older adults (n = 194; mean [standard deviation] age = 78.93 [9.10]) was assessed by the Geriatric Oral Health Assessment Index and the Oral Health Impact Profile questionnaires. Prosthetic rehabilitation status was recorded according to the absence of teeth and use of dental prostheses. Dental prosthesis condition was considered good or poor based on stability, retention, occlusion, vertical dimension, and defects. Poisson regression models were plotted to analyze the data (α = 0.05). Results:Lower Geriatric Oral Health Assessment Index scores were associated with edentulism with denture use only on one jaw (B = -0.05) and poor dental prosthesis stability (B = -0.04). Similarly, edentulous participants with denture only on one jaw (B = 0.59) and those wearing dental prostheses with poor stability (B = 0.36) are more likely to achieve higher Oral Health Impact Profile scores. Also, lower Oral Health Impact Profile scores were associated with denture defects (B = -0.34). Conclusion:In summary, the oral health-related quality of life of older adults living in long-term care facilities is negatively impacted by edentulism with denture only on one jaw and use of dental prostheses with poor stability. Therefore, long-term care facilities should provide oral health training to caregivers, include dental professionals in the staff, and articulate demands with oral health teams in the primary care system.